2021
DOI: 10.3390/rs13020232
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Yield Mapping Using High-Resolution Imagery Data and Machine Learning Technique

Abstract: Yield maps provide essential information to guide precision agriculture (PA) practices. Yet, on-board yield monitoring for sugarcane can be challenging. At the same time, orbital images have been widely used for indirect crop yield estimation for many crops like wheat, corn, and rice, but not for sugarcane. Due to this, the objective of this study is to explore the potential of multi-temporal imagery data as an alternative for sugarcane yield mapping. The study was based on developing predictive sugarcane yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 50 publications
5
38
0
2
Order By: Relevance
“…They analyze crop attributes and estimate crop production during the harvest. Optical sensors, such as OptRx [58], Cloro-fiLOG [59], Dualex [27], Multiplex [60], Isaria, Crop Circle [61], SPAD-502 [10], Crop-Spec [62], GreenSeeker [63], and ALS-2 N [10], provide crop monitoring under day and night conditions [64], as shown in Table 1. The method of analysis involves collecting a large quantity of recordings per field with many measurements per second [65].…”
Section: Optical Sensorsmentioning
confidence: 99%
“…They analyze crop attributes and estimate crop production during the harvest. Optical sensors, such as OptRx [58], Cloro-fiLOG [59], Dualex [27], Multiplex [60], Isaria, Crop Circle [61], SPAD-502 [10], Crop-Spec [62], GreenSeeker [63], and ALS-2 N [10], provide crop monitoring under day and night conditions [64], as shown in Table 1. The method of analysis involves collecting a large quantity of recordings per field with many measurements per second [65].…”
Section: Optical Sensorsmentioning
confidence: 99%
“…Through the mass flow predicted, it is possible to calculate the yield in a given area (e.g., ton ha −1 ), and together with the coordinates, yield maps can be generated. Yield maps are the key to managing sugarcane spatial variability [ 5 , 6 ]. This is the starting point for implementing Precision Agriculture (PA) practices, which aim to assist decision-making and interventions in high spatial definition in the agricultural fields.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that more efforts were necessary to modelling mechanistically other significant physiological processes such as nitrogen distribution and uptake, and leaf and tiller senescence. Other researchers (Gao et al, 2020, Canata et al, 2021, Mobe et al, 2021 used some parameters such as weather temperature, soil moisture, etc. to predict barley growth stages.…”
Section: Introductionmentioning
confidence: 99%